WORD PICKER AS A VOCABULARY ENHANCER FOR WEAK STUDENTS IN A SECONDARY CLASSROOM - Amrit Kaur, Maria Shu Hong Bee Abdullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Students love to take part in classroom discussions and activities, but when English as Second Language (ESL) students with limited English vocabulary are ostracized because they cannot properly participate, this causes their confidence to suffer. The challenges usually lie in the lack of vocabulary among students which lead to the poor performances in the English language and this calls for immediate attention. This paper will discuss the use of a strategy the Word Picker to improve the vocabulary among the ESL weak students in a secondary school in Malaysia. Data collected via questionnaire, document analysis and video recordings were analysed qualitatively. The findings suggested that the Word Picker strategy has helped the weak ESL students to enhance their vocabulary skills